Effects of non‐amputative wide local excision on the local control and prognosis of in situ and invasive subungual melanoma. Issue 9 (18th May 2015) - Nakamura, Yasuhiro; Ohara, Kuniaki; Kishi, Akiko; Teramoto, Yukiko; Sato, Sayuri; Fujisawa, Yasuhiro; Fujimoto, Manabu; Otsuka, Fujio; Hayashi, Nobukazu; Yamazaki, Naoya; Yamamoto, Akifumi
Abstract Subungual melanomas (SUM) are rare, and amputation is often required. Non‐amputative wide local excision (WLE) of the nail unit with the periosteum of the distal phalanx, followed by skin graft, has been accepted for in situ or SUM of 0.5 mm or less thickness. However, previous reports have included a limited number of cases, and not all more than 0.5‐mm thick SUM exhibit invasion or attachment to the distal phalanx. The aim of the present study was to investigate the local recurrence and prognosis for in situ, minimally invasive and invasive SUM that were treated using WLE. We retrospectively reviewed 50 patients with in situ (n = 48) or minimally invasive SUM (n = 2) (in situ or minimally invasive group) and 12 patients with more than 0.5‐mm thick invasive SUM (invasive group) who were treated using WLE. All patients survived the follow‐up period (24–207 months), although four patients with in situ SUM experienced local recurrence at the lateral margin and re‐excision was required. In the invasive group, no patients experienced local recurrence, although one patient (8.3%) developed nodal metastasis at 86 months and regional lymph node dissection was required. WLE may provide acceptable local control for in situ and intermediate thickness SUM, without compromising the vital prognosis. However, a larger randomized prospective study with long‐term follow up is required to evaluate adequately the risks associated with a non‐amputative WLE for in situ and invasive SUM.